Dietary patterns associated with hyperuricemia among the southeast coastal Chinese population - Basnet, Til Bahadur; Su, Qingling; Gong, Jiamin; Huang, Xiaoyin; Li, Wanxin; Chen, Jun; Feng, Ruimei; Du, Shanshan; Yang, Haomin; Ye, Weimin (Frontiers in Nutrition, 2025)
IntroductionVarious foods or food groups and nutrients are correlated with serum uric acid levels. However, the findings were not consistent across different populations, and the mechanisms remain unclear.MethodsIn the baseline survey of the Fuqing Cohort, 4,326 participants were selected from Southeast coastal Chinese communities, and their dietary patterns were derived from a validated food frequency questionnaire using principal component analysis. Logistic regression was used to estimate the risk of hyperuricemia across the quintiles of each dietary pattern. Additionally, we performed mediation analysis to assess the potential mediating role of metabolic factors.ResultsBased on the parallel analysis, four principal components were retained, explaining 46% of the total variance. Higher consumption of animal-based food (meat, fish, and seafood), bean products, sweets, desserts, and fried foods is significantly associated with an increased risk of hyperuricemia (Odds ratio for highest quintile of this dietary pattern vs. lowest: 1.36; 95% CI: 1.07, 1.72). Participants under 60 years showed a notably higher relative risk, which was significantly mediated by body mass index in combination with low-density lipoprotein and/or fatty liver.ConclusionGreater adherence to a high-protein diet, along with fried food, sweets, and desserts, increases the risk of hyperuricemia, particularly in people under 60 years of age. Moderate consumption of an animal-based diet and significantly reducing the intake of sweets and fried foods may help prevent the risk of hyperuricemia.